Automatic measurement methane by displacement columns - Vaquerano-Pineda, Nicolás (2016)
It describes an automatic process implemented through the use of the Siemens LOGO controller for measuring volume, flow and methane concentration in biogas produced by cellulosic substrates. It determines the composition of biogas without the time consuming and unnecessarily detailed chromatography method. Due to the interest in methane in biogas, a technique has been developed by means of displacement columns for determining volume and low flow. An indirect procedure has been implemented to estimate high proportions of methane, using inexpensive sensors designed for concentrations of 1% in volume.